Analysis of serum macrophage migration inhibitory factor and D‐dopachrome tautomerase in systemic sclerosis. Issue 12 (6th December 2018) - Vincent, Fabien B; Lin, Emily; Sahhar, Joanne; Ngian, Gene‐Siew; Kandane‐Rathnayake, Rangi; Mende, Rachel; Hoi, Alberta Y; Morand, Eric F; Lang, Tali; Harris, James
Abstract: Objectives: Macrophage migration inhibitory factor (MIF) and D‐dopachrome tautomerase (DDT), members of the same cytokine superfamily, are linked to the pathogenesis of a number of inflammatory diseases. The aim of this study was to investigate their clinical relevance in systemic sclerosis (SSc). Methods: Serum MIF and DDT were quantified in 105 SSc patients by ELISA and levels compared to healthy controls (HC) (47) and patients with systemic lupus erythematosus (SLE) (184). Clinical parameters included organ involvement, serum laboratory markers and results of pulmonary function tests, and overall disease activity assessed using the European Scleroderma Trials and Research group (EUSTAR) activity index. Results: There was no significant difference in serum DDT concentrations between patients with SSc and HC. However, serum MIF was significantly increased in SSc compared to both HC and SLE cohorts. Serum MIF was increased in SSc patients with low forced vital capacity (FVC) and was also associated with the use of angiotensin II receptor blockers and beta blockers in SSc, confirmed after adjusting for the presence of systemic hypertension and low FVC. Serum DDT was significantly higher in SSc patients with low FEV1 and negatively correlated with EUSTAR score, particularly in patients with limited disease. Conclusion: Although not significantly linked to specific clinical parameters, serum MIF was significantly higher in SSc patients than in HC and SLE patients, suggesting a fundamental role for MIF in SSc. DDT, while closely related to MIF, did not show a similar expression profile, suggesting functional differences between these molecules. Abstract : We found that macrophage migration inhibitory factor (MIF), but not D‐dopachrome tautomerase (DDT), was significantly raised in the serum of patients with systemic sclerosis (SSc) compared to both healthy controls and patients with systemic lupus erythematosus (SLE). High serum MIF was linked to low forced vital capacity and the use of angiotensin II receptor blockers and beta blockers, independent of systemic hypertension.